2021
DOI: 10.1002/aet2.10675
|View full text |Cite
|
Sign up to set email alerts
|

Development of a health equity journal club to address health care disparities and improve cultural competence among emergency medicine practitioners

Abstract: Health care disparities have been magnified by the COVID-19 pandemic. Only recently has the medical community acknowledged implicit bias and systemic racism as a public health emergency. Graduate medical education has been slow to adopt curricula beyond lecture-based formats that specifically address social determinants of health (SDOH) and its impact on communities. Curricula addressing unconscious (implicit) biases and their influence on patient care has not been widely adopted. The emergency department (ED)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the preconference literature review, we found articles in the literature that highlight strategies for addressing racism and racial bias on internalized, interpersonal, institutional, and systemic levels 26,44–52 . Much of the literature focused on describing workshops and efforts to address racism in health care and diversity in recruitment of health care professionals 45,47,48,50,51 . While several of the available articles raise awareness of issues and provide suggestions for interventions, few articles exist with data measuring the impact of such interventions 53,54 .…”
Section: Consensus Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the preconference literature review, we found articles in the literature that highlight strategies for addressing racism and racial bias on internalized, interpersonal, institutional, and systemic levels 26,44–52 . Much of the literature focused on describing workshops and efforts to address racism in health care and diversity in recruitment of health care professionals 45,47,48,50,51 . While several of the available articles raise awareness of issues and provide suggestions for interventions, few articles exist with data measuring the impact of such interventions 53,54 .…”
Section: Consensus Findingsmentioning
confidence: 99%
“…In the preconference literature review, we found articles in the literature that highlight strategies for addressing racism and racial bias on internalized, interpersonal, institutional, and systemic levels. 26,[44][45][46][47][48][49][50][51][52] Much of the literature focused on describing workshops and efforts to address racism in health care and diversity in recruitment of health care professionals. 45,47,48,50,51 While several of the available articles raise awareness of issues and provide suggestions for interventions, few articles exist with data measuring the impact of such interventions.…”
Section: Cons Ensus Finding S Research Gap Domain 1: Remedies For Bia...mentioning
confidence: 99%
See 2 more Smart Citations
“…web-based, interactive teaching sessions, etc.). [16][17][18][19] Care should also be taken in maintaining learners' psychological safety. Implementation of implicit bias training within UME/ GME increases trainee awareness of their individual implicit biases but may also induce stress when learners begin to recognize bias within themselves.…”
mentioning
confidence: 99%